IJARAH AND RIBA IN THE SHARIA CARD: Analysis Of ‘Illat Hukmi Of Sharia Card In The Adz-Dzari’ah Perspective - Syaifuddin Zuhdi; Dania Nalisa Indah; Dewati Candraningtyastuti; Tsurayya Shafa Kamila (Muhammadiyah University Press, 2021)
Purpose: This article aims to analyze whether the imposition of ijarah (membership fee) in the sharia card belongs to the practice of usury, which will later affect Adz-Dzari’ah’s view of the permissibility of using sharia card.Method: This research employed a normative method by obtaining information from various scientific literature sources as well as national and Islamic law materials.Findings: Indonesia allows sharia card usage based on the concept of Adz-Dzari’ah following the ‘illat (legal or basic cause) attached to establish the banking products. In addition, it is also considered whether, in practice, there are also some acts considered usury, especially in the addition of fees due to ijarah imposed by the issuer on the user.Practicality: This article is intended for academics and practitioners in Islamic economic law, especially for sharia banking activists.Novelty/Originality: In essence, ijarah can be utilized as a variable to influence one’s opinion on Islamic law from a sharia perspective since the advantages exceed the risks, and it is preferable to allow it than forbid it. However, these permits are also issued when new or revised rules are being developed or revised. Concerning procurement, not only in the MUI fatwa but also in the sharia card, the law is written to be utilized as a legal foundation binding the associated parties and providing broad legal recommendations. Additionally, it will bolster the Fath Adz-Dzari’ah position on the permissibility of using the sharia card since the specifications of its contents will almost definitely be more precise to avoid a legal vacuum.